تطبيقات مقصد العرض المعاصرة: دراسة مقاصدية قانونية - الربابعة، أسامة حسن محمد; الشوابكة، فيصل عبدالحافظ; الربابعة، أحمد حسن (جامعة آل البيت, 2019)
يهدف البحث إلى بيان أثر البصمة الوراثية، في المحافظة على مقصد حفظ العرض، من الناحيتين: المقاصدية والقانونية، وقد اشتمل على مقدمة، وتعريف بالمشكلة، وبيان ماهية الدراسات السابقة، والإضافات العلمية التي أضافها البحث، وذكر منهجية البحث وخطته. وقد جاءت الدراسة بمبحثين، حيث اشتمل المبحث الأول: على مقصد حفظ العرض، والأحكام المتعلقة به، وانطوت تحته ثلاثة مطالب المطلب، الأول: مصطلح مقصد حفظ العرض لغة واصطلاحا، والمطلب الثاني: جانب الوجود، المتعلقة بالمحافظة على مقصد حفظ العرض، والمطلب الثالث: جانب العدم، المتعلقة بالمحافظة على مقصد حفظ العرض، ثم المبحث الثاني: أثر البصمة الوراثية، في المحافظة على مقصد حفظ العرض، وقد اشتمل على مطلبين: المطلب الأول: مفهوم البصمة الوراثية لغة واصطلاحا، ومشروعيتها، أما المطلب الثاني: فهو دور البصمة الوراثية، في المحافظة على مقصد حفظ العرض، ثم خاتمة بأهم النتائج والتوصيات التي توصلنا إليها.
This research aims, to demonstrate the impact of DNA, to maintain the intent of keeping the offspring, both: teleology and legaley, has included an introduction to the research, and the definition of the problem, and the idea of the previous studies, and scientific additions added by the search, and the explanation of the methodology and plan of the research. The study consists of two sections, the first section, the purpose of keeping the offspring, and conditions related to it, which is three chapters: Chapter One: The term intent of keeping the offspring, linguistically and idiomatically, and the second: positive provisions, relating to the conservation intent of keeping the offspring, and the third negative conditions , relating to the conservation intent of keeping the offspring, then the second chapter: the impact of DNA, to preserve the intent of keeping the offspring, and Hovslan: first: the concept of DNA, linguistically and idiomatically, and legitimacy, and the second: the role of DNA in preserving the intent of keeping the offspring, then the conclusion of the most important results and recommendations that we reached.
Keywords: حفظ العرض -- البصمة الوراثية -- المقاصدية والقانونية -- المقاصد الشريعة